ANALISIS FRAMING PEMBERITAAN MENGENAI KEBAKARAN HUTAN DAN LAHAN DI KALIMANTAN BARAT DALAM WWW.KALBAR.ANTARANEWS.COM - Yunita Andriani; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis article is entitled "Analysis of News Framing Related to Forest and Land Fires in West Kalimantan in www.kalbar.antaranews.com". This article was conducted by analyzing news which aims to describe news framing with the issue of forest and land fires at www.kalbar.antaranews.com. The method used in this research is a descriptive method with a qualitative research form. The data sources for this research are the writers and news editors of www.kalbar.antaranews.com. The techniques used in this research are interview, note-taking, and documentary studies. The tools used in this study were a list of questions, notebooks, writing instruments, and a recording device used for documentation, namely gadgets. The results of data analysis at www.kalbar.antaranews.com are media that support the government's efforts, one of which is anticipating forest and land fires. Based on 10 reports on forest and land fires on www.kalbar.antaranews.com, Robert N Entman's research has a framing with four elements, namely defining the problem, diagnosing the cause (estimating the problem or source of the problem), making moral judgments (making decisions). morals), and treatment recommendations (emphasizing completion). The form of the Indonesian text is based on an analysis of the framing of news on forest and land fires.Keywords: News, Framing, Forest and Land Fires